Tkinter GUI application development hotshot : develop exciting and engaging GUI applications in Python and Tkinter by working on 10 real-world applications /: develop exciting and engaging GUI applications in Python and Tkinter by working on 10 real-world applications. (©2013) - Unknown
No abstract available